Genetic Dissection of a Prevalent Plasmid-Encoded Conjugation System in Lactococcus lactis - Ortiz Charneco, Guillermo; Kelleher, Philip; Buivydas, Andrius; Streekstra, Hugo; van Themaat, Emiel Ver Loren; de Waal, Paul P.; Mahony, Jennifer; van Sinderen, Douwe (Frontiers in Microbiology, 2021)
Plasmid pNP40, which was first identified nearly forty years ago in Lactococcus lactis subsp. lactis biovar diacetylactis DRC3, encodes functions such as heavy metal-, bacteriophage- and nisin-resistance, as well as horizontal transfer ability by conjugation. Here, we report an optimized conjugation protocol for this plasmid, yielding a transfer frequency that is approximately 4,000-fold higher than those previously reported in literature, while we also observed high-frequency plasmid co-mobilisation. Individual mutations in 18 genes that encompass the presumed conjugation cluster of pNP40 were generated using ssDNA recombineering to evaluate the role of each gene in the conjugation process. A possible transcriptional repressor of this conjugation cluster, the product of the traR gene, was identified in this manner. This mutational analysis, paired with bioinformatic predictions as based on sequence and structural similarities, allowed us to generate a preliminary model of the pNP40 conjugation machinery.